Cause for concern - Stephen M. Adler
Can 'cause marketing' help you succeed? CAUSE FOR CONCERN: RESULTS-ORIENTED CAUSE MARKETING shows you how. Author Stephen M. Adler expertly reveals to you how cause marketing works, why it makes sense for businesses, and how to make a profit using cause marketing. And he also includes special sections on the ethics of cause marketing as well. Plus, CAUSE FOR CONCERN: RESULTS-ORIENTED CAUSE MARKETING is easy-to-read and full of study tools, so you'll be able to succeed on the test also!